2008
DOI: 10.1007/s12013-008-9020-9
|View full text |Cite
|
Sign up to set email alerts
|

Extremely High Frequency Electromagnetic Radiation Enforces Bacterial Effects of Inhibitors and Antibiotics

Abstract: The coherent electromagnetic radiation (EMR) of the frequency of 51.8 and 53 GHz with low intensity (the power flux density of 0.06 mW/cm(2)) affected the growth of Escherichia coli K12(lambda) under fermentation conditions: the lowering of the growth specific rate was considerably (approximately 2-fold) increased with exposure duration of 30-60 min; a significant decrease in the number of viable cells was also shown. Moreover, the enforced effects of the N,N'-dicyclohexylcarbodiimide (DCCD), inhibitor of H(+)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 34 publications
1
35
0
Order By: Relevance
“…Bacterial resistance to one or more antibiotics occurs by various mechanisms (24)(25)(26). In this way, EMFs as an environmental agent could influence cellular responses such as antimicrobial susceptibility through different pathways (4,20,22,23,27). The aim of the present study was to evaluate the antimicrobial susceptibility of K. pneumoniae under 900 MHz radiofrequency radiations condition.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial resistance to one or more antibiotics occurs by various mechanisms (24)(25)(26). In this way, EMFs as an environmental agent could influence cellular responses such as antimicrobial susceptibility through different pathways (4,20,22,23,27). The aim of the present study was to evaluate the antimicrobial susceptibility of K. pneumoniae under 900 MHz radiofrequency radiations condition.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial effects of extremely high frequency EMI might be explained by EMI effects on membrane structure and function [13][14][15], water properties [2,8,16,17], and on genome or DNA [18][19][20][21] and/or by the EMI transformation into informative biological signals at specific resonant frequencies [3,13,22]. Besides, extremely high frequency EMI can be used as a convenient band for communications within and between bacteria [3,22].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3]. According to literature, the millimeter-wave therapy increases the level of immune resistance, influences different stages of pathogenesis, changes enzymatic reaction activity and growth rate, destroys microorganisms, and increases the thermostability of DNA [4][5][6]. The literature has shown that millimeter waves have strong effect on the process and bioelectric activity of neurochemical functions of the brain, increase the cortical tension, and influence the spike activity of neurons in the supraoptic nucleus of the hypothalamus in rats [7,8].…”
Section: Introductionmentioning
confidence: 99%